Students' Career Counseling - A Need in Contemporary Universities. Career Counseling Services Provided By Career Counseling Center of Bucharest University of Economic Studies - Camelia STĂICULESCU; Maria Liana LĂCĂTUŞ; Ramona Elena RICHIŢEANU NĂSTASE (Revista de Management Comparat International)
In a world of diversity, that is changing permanently, universities have to adapt to the needs of their beneficiaries and to provide a multitude of high quality services. The paper presents the need of providing counseling for students, teachers, and employers too so that the educational supply of the university to meet the employers’ and labor market ‘s needs and graduates to be able to integrate and develop themselves socially and professionally in an adequate manner, and students do not give up to their studies. The paper also analyses the counseling services provided by Career Counseling Center of Bucharest University of Economic Studies as an example of good practices.